2013
DOI: 10.1016/j.joca.2013.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Safety of intra-articular cell-therapy with culture-expanded stem cells in humans: a systematic literature review

Abstract: Based on current literature review we conclude that application of cultured stem cells in joints appears to be safe. We believe that with continuous caution for potential side effects, it is reasonable to continue with the development of articular stem cell therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
110
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(114 citation statements)
references
References 40 publications
(34 reference statements)
3
110
1
Order By: Relevance
“…They divided patients in 3 groups, administrating 10×10e 6 , 50×10e 6 and 100×10e 6 MSC. The outcomes showed intra-articular knee injection of 100×10e 6 autologous MSC improved function and pain as well as cartilage defects by regeneration of hyaline-like articular cartilage [56].…”
Section: Discussionmentioning
confidence: 99%
“…They divided patients in 3 groups, administrating 10×10e 6 , 50×10e 6 and 100×10e 6 MSC. The outcomes showed intra-articular knee injection of 100×10e 6 autologous MSC improved function and pain as well as cartilage defects by regeneration of hyaline-like articular cartilage [56].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a systematic review of the literature was published which evaluated the safety of cell therapies expanded in culture for intraarticular use in humans [23]. It was concluded that the application of cultured cells in human joints seems to be a safe procedure.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 This progression consisted of injecting all sorts of agents that induce a biological response, including: dextrose, sodium bicarbonate/calcium gluconate, hyaluronic acid, platelet rich plasma (PRP), bone marrow aspirate concentrate (BMAC), nano or micronized fat, adipose-stromal vascular fraction (A-SVF), culture expanded meschymal stem cells (CE-MSCs) both allogenic as well as autologous from a multitude of sources are becoming more commonplace. 16 The aggregate number and quality of studies are steadily improving, it is no doubt that the application of the cells are safe 10,12,21,22 and efficacious. 16 …”
Section: History Of Regenerative Medicine-cartilagementioning
confidence: 99%
“…[35][36][37][38] The basis for intervention has been the interpretation of stem cell therapies as high-risk biologic treatments despite data to the contrary. 10,12,21,22,39 Although an increasing number of warning letters to multiple clinics have been sent by the FDA, there are still numerous facilities that are operational and offering a full range of treatments to include administration of culture expanded cells, SVF delivered by intraarticular, intravenous, epidural, intra-discal, as well intrathecal transplantations. The US-FDA divides biologic therapies into low-risk and high-risk therapies by determining if the product has undergone minimal manipulation and autologous use (Fig.…”
Section: Regulatory Implications Facing Cartilage Regenerative Medicinementioning
confidence: 99%